Pelle (C44) Carcinoma a cellule di Merkel linfonodale in assenza di lesioni cutanee evidenti: report di tre casi e revisione della letteratura / Lymph node Merkel cell carcinoma with no evidence of cutaneous tumor: report of three cases and review of the literature - Panetta, A.; Avveniente, A.; Pajetta, et al., V. (European Journal of Oncology and Environmental Health, 2011)
Il carcinoma a cellule di Merkel (MCC) è un raro tumore maligno della cute. Tuttavia, sono stati descritti casi sporadici di localizzazioni linfonodali di MCC senza evidenti lesioni cutanee. Pertanto, la possibilità di una localizzazione primitiva linfonodale del MCC è attualmente presa in considerazione. Riportiamo tre casi di MCC con presentazione linfonodale in assenza di una sede primitiva cutanea. Viene presentata, inoltre, una revisione della letteratura. Lymph node Merkel cell carcinoma with no evidence of cutaneous tumor: report of three cases and review of the literature Merkel cell carcinoma (MCC) is a rare malignancy tumor of the skin. However, sporadic cases of lymph nodal localizations of MCC have been described without any evident cutaneous lesions. Therefore, the possibility of primary lymph nodal MCC is currently taken into consideration. We report three cases of MCC presenting in the lymph nodes in the absence of a primary cutaneous site. A review of the literature is also presented.